Recent sarcopenia definitions—prevalence, agreement and mortality associations among men: Findings from population‐based cohorts. Issue 1 (5th January 2023) - Westbury, Leo D.; Beaudart, Charlotte; Bruyère, Olivier; Cauley, Jane A.; Cawthon, Peggy; Cruz‐Jentoft, Alfonso J.; Curtis, Elizabeth M.; Ensrud, Kristine; Fielding, Roger A.; Johansson, Helena; Kanis, John A.; Karlsson, Magnus K.; et al.
Abstract: Background: The 2019 European Working Group on Sarcopenia in Older People (EWGSOP2) and the Sarcopenia Definitions and Outcomes Consortium (SDOC) have recently proposed sarcopenia definitions. However, comparisons of the performance of these approaches in terms of thresholds employed, concordance in individuals and prediction of important health‐related outcomes such as death are limited. We addressed this in a large multinational assembly of cohort studies that included information on lean mass, muscle strength, physical performance and health outcomes. Methods: White men from the Health Aging and Body Composition (Health ABC) Study, Osteoporotic Fractures in Men (MrOS) Study cohorts (Sweden, USA), the Hertfordshire Cohort Study (HCS) and the Sarcopenia and Physical impairment with advancing Age (SarcoPhAge) Study were analysed. Appendicular lean mass (ALM) was ascertained using DXA; muscle strength by grip dynamometry; and usual gait speed over courses of 2.4–6 m. Deaths were recorded and verified. Definitions of sarcopenia were as follows: EWGSOP2 (grip strength <27 kg and ALM index <7.0 kg/m 2 ), SDOC (grip strength <35.5 kg and gait speed <0.8 m/s) and Modified SDOC (grip strength <35.5 kg and gait speed <1.0 m/s). Cohen's kappa statistic was used to assess agreement between original definitions (EWGSOP2 and SDOC). Presence versus absence of sarcopenia according to each definition in relation to mortality risk was examined using Cox regression with adjustment for age and weight; estimates were combined across cohorts using random‐effects meta‐analysis. Results: Mean (SD) age of participants ( n  = 9170) was 74.3 (4.9) years; 5929 participants died during a mean (SD) follow‐up of 12.1 (5.5) years. The proportion with sarcopenia according to each definition was EWGSOP2 (1.1%), SDOC (1.7%) and Modified SDOC (5.3%). Agreement was weak between EWGSOP2 and SDOC (κ = 0.17). Pooled hazard ratios (95% CI) for mortality for presence versus absence of each definition were EWGSOP2 [1.76 (1.42, 2.18), I 2 : 0.0%]; SDOC [2.75 (2.28, 3.31), I 2 : 0.0%]; and Modified SDOC [1.93 (1.54, 2.41), I 2 : 58.3%]. Conclusions: There was low prevalence and poor agreement among recent sarcopenia definitions in community‐dwelling cohorts of older white men. All indices of sarcopenia were associated with mortality. The strong relationship between sarcopenia and mortality, regardless of the definition, illustrates that identification of appropriate management and lifecourse intervention strategies for this condition is of paramount importance.